Genes of the extinct Caucasian bison still roam the Białowieża Forest and are the source of genetic discrepances between Polish and Belarusian populations of the European bison, Bison bonasus. (23rd January 2015) - Tokarska, Małgorzata; Bunevich, Aleksei N.; Demontis, Ditte; Sipko, Taras; Perzanowski, Kajetan; Baryshnikov, Gennady; Kowalczyk, Rafał; Voitukhovskaya, Yuliya; Wójcik, Jan Marek; Marczuk, Barbara; Ruczyńska, Iwona; Pertoldi, Cino
<x xml:space="preserve">Abstract</x> European bison (Bison bonasus) populations from both the Polish (PL) and the Belarusian (BY) sides of the Białowieża Forest represent the Lowland genetic line (LB line) – progeny of the Lowland bison (Bison bonasus bonasus) that inhabited western, central, and south‐eastern Europe in historical times. During the species recovery, one of the founders was a descendant of the extinct Caucasian bison (Bison bonasus caucasicus) and its descendants formed the other genetic line – Lowland–Caucasian (LC). There have been justified suspicions that LB European bison in the former Soviet Union had undergone cross‐mating with the LC line. We performed a comparative genetic analyses on European bison from the BY and PL parts of the Białowieża Forest, the LC line and extinct Caucasian bison, based on a set of 19 microsatellite markers and 1512 bovine single nucleotide polymorphism (SNP) markers, polymorphic in at least one of the studied populations. Although genetic variability (mean allele number and expected heterozygosity) for both populations were similar, the FST jack‐knifing and principal component analyses PCA revealed highly significant differences between PL and BY bison from the Białowieża Forest. Examining DNA of the extinct Caucasian bison revealed that at least part of the genetic variants found in the BY, but not the PL, population were of Caucasian origin. The results indicate that the contemporary population of European bison from the BY part of the Białowieża Forest should not be regarded as a LB line. The results also suggest that the actual global population size of the LB line European bison is only a half of its official status. Consideration of the presented results are crucial in determining management actions and policy decisions in order to conserve LB line bison within the Białowieża Forest – its natural refuge. © 2015 The Linnean Society of London, Biological Journal of the Linnean Society, 2015, 114, 752–763.